(untitled) (International Journal of Irrigation and Water Management, 2014)
In upland areas of Northern Thailand, lychee (Litchi chinensis, Sonn.) is one of the predominant fruit crops. Fruit development takes place during the dry season (January until June). Therefore, high lychee yields can only be obtained under irrigation. As water is an increasingly scarce resource in the hillsides, strategies for more efficient water use are fundamental for a sustainable increase in agricultural production. An Automatic Tensio Control (ATC) unit was developed to use soil matric potential to open and close the inlet valve of a micro-irrigation lateral. In order to test the functioning of the ATC in the field, four different irrigation regimes have been tested in cooperation with local farmers on 10 year old lychee trees on a commercial orchard in Mae Sa Mai, close to Chiang Mai, Thailand. Testing the ATC on station and under field conditions, it has proven its reliability in maintaining a favorable moisture regime in the soil. The irrigated lychee trees responded to ATC irrigation with a higher yield and higher fruit weight compared to the other treatments. ATC works without electric components, so that it can be operated in areas without electricity. Furthermore, it is assembled from cheap and simple materials. Thus, it can be easily copied and adapted to different agro-ecological and socio-economic environments.